Stomoxys calcitrans (Diptera:Muscidae) biology in byproducts of sugar cane industry - Mendes, Camila de Oliveira Ferreira; Silva, Amanda Couto; Leal, Luís Carlos de Souza Rodrigues; Barbosa, Celso Guimarães; Bittencourt, Avelino José (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Mendes C.deO.F., Silva A.C., Leal L.C.deS.R., Barbosa C.G & Bittencourt A.J. [Stomoxys calcitrans (Diptera:Muscidae) biology in byproducts of sugar cane industry.] Biologia de Stomoxys calcitrans (Diptera:Muscidae) em subprodutos da indústria sucroalcoleira. Revista Brasileira de Medicina Veterinária, 38(supl. 3):23-30, 2016. Departamento de Medicina e Cirurgia Veterinária, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, BR 465, Km 7, Campus Seropédica, RJ 23.890-000, Brasil. E-mail: camilamendes1009@gmail.com Stomoxys calcitrans fly is one of the dipterans of importance for livestock farming due to the considerable economic losses it determines worldwide. An aspect that favors the occurrence of this insect’s outbreaks in Brazil is the generation of large quantities of by-products from the alcohol industry, such as vinasse, sugarcane straw, bagasse, filtercake and ashes. The present study aimed to evaluate the possible interference of vinasse and ashes on the immature stages of S. calcitrans, by comparing the biological parameters observed with or without the presence of these substrates. In Experiment I, three groups of 50 eggs were deposited in a diet composed of one kilogram of chopped cane and 250mL, 500mL and 1L of vinasse (groups 1, 2 and 3). In the control groups, distilled water was added to the chopped cane in the same proportions used in the groups treated with vinasse. In Experiment II, three groups of 50 larvae from eight to 10 days of emergence were deposited on a diet composed of cane, vinasse and ashes. The ashes were used in the proportion of 1, 2 and 3% (groups 1, 2 and 3) of sugar cane (100g) and vinasse was used in the proportion of 100mL for all groups and their respective controls. The control group contained only sugarcane and vinasse. Both experiments were kept in a climatized chamber (27 ± 1°C and 70-80% RH), and three replications were performed. After Experiment I, it was verified that the emergence of flies started more rapidly in Group 3 (17.33 days). The viability in Experiment I was lower in all groups in which vinasse was added in sugarcane, ranging from 20.66-34%, when compared to its controls (26.66-34.66%). In Experiment II, the onset of emergence of the flies was at seven days in all groups, lasting between 12.33 and 14 days on average, being lower for the groups that contained ashes in the diet. The viability in Experiment II was high in all groups with ashes (above 74%) and in the control, which presented greater viability (87%). When evaluating the emergence of males and females in Experiment I and II, it was observed that in all treated and control groups more females than males occurred. The evaluation of the data in the Experiment I allows the conclusion that vinasse can cause an early onset of the emergence of adults, but this emergency has a short duration. In Experiment II, ashes did not influence the onset of adult emergence, where the treated groups began their emergence at the same time as their control, while reducing the emergency period. Vinasse and ashes can interfere negatively in the development of immature stages of S. calcitrans, causing lower viability values for this insect.